2022
DOI: 10.1038/s41528-022-00140-4
|View full text |Cite
|
Sign up to set email alerts
|

On-skin ultrathin and stretchable multifunctional sensor for smart healthcare wearables

Abstract: The flexible and stretchable multifunctional sensors for the precise monitoring of the human physiological health indicators is an emerging requirement of next-generation electronics. However, the integration of multifunctional sensors into a common substrate for simultaneous detection of such signals without interfering with each other is the most challenging work. Here, we propose MXene-Ti3C2Tx and 3, 4-ethylene dioxythiophene (EDOT) deposited on laser-induced graphene (LIG/MXene-Ti3C2Tx@EDOT) composite-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(77 citation statements)
references
References 57 publications
1
66
0
Order By: Relevance
“…Hence, the contribution from the thermal expansion of the PET was considered negligible. 47 Because the developed adhesive sensors are intended to be used for body temperature monitoring, the printed sensors were assessed between 30 and 42 °C. In the window of the study, all the sensors prepared with different volume fractions of fillers demonstrated a decrease in the resistance with an increase in the temperature (negative temperature of coefficient behavior).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the contribution from the thermal expansion of the PET was considered negligible. 47 Because the developed adhesive sensors are intended to be used for body temperature monitoring, the printed sensors were assessed between 30 and 42 °C. In the window of the study, all the sensors prepared with different volume fractions of fillers demonstrated a decrease in the resistance with an increase in the temperature (negative temperature of coefficient behavior).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The developed sensor was not encapsulated. Hence, the contribution from the thermal expansion of the PET was considered negligible . Because the developed adhesive sensors are intended to be used for body temperature monitoring, the printed sensors were assessed between 30 and 42 °C.…”
Section: Resultsmentioning
confidence: 99%
“…In 2021, Guo et al [ 25 ] developed the design and production of dual microstructures of surface micro-bumps and internal hollow pores in the conductive material, MXene, to obtain a multifunctional high-performance pressure sensor, showing an ultra-sensitive ability to extract gesture behavioral information and physiological information from the sensor signals, and its implications for human health. In 2022, Zhang et al [ 26 ] developed an on-skin ultrathin and stretchable multifunctional sensor for smart medical wearables that paves a promising path for future wearables for smart skin and healthcare applications. The above discussion briefly outlines the timeline of major milestones in the development of flexible sensors in the smart wearable field ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Conductive materials have attracted increasing attention in stretchable sensors owing to their high conductivity, cost-effectiveness, excellent mechanical properties, and ease of processability [ 1 , 2 ]. Even though on-skin sensors based on highly conductive materials show small resistance changes in strain sensors for small input signals compared to low-conductivity materials, they have exceptional merits in terms of low power consumption, fast response, and low hysteresis [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%